Lessons from an Educational Game Usability Evaluation - Perry, Gabriela Trindade; Kulpa, Ci Costa; Pinheiro, Eluza; Eichler, Marcelo Leandro (International Journal of Interactive Mobile Technologies (iJIM), 2012)
In this paper, we present the results of a usability evaluation for Xenubi, a cell phone game about the periodic table. We describe and discuss the issues that we faced during the evaluation, which took place in a state high school. These issues are related to conflicts between the data that were gathered through video recordings and through a questionnaire. We also point to the poor performance of the game mechanics during the evaluation. This result was unexpected because the game had an excellent performance in the pilot test. Possible causes for these differences are discussed.